Political legitimacy and housing : stakeholding in Singapore - Chua, Beng Huat (Routledge, 1997)
Looking at the ways in which Singapore's planners have dealt with the problems of creating communities in a modern urban environment, the author concludes that the success of the public housing programme has done much for the nation. Singapore's successful public housing programme is a source of political legitimacy for the ruling People's Action Party. Beng-Huat Chua accounts for the success of public housing in Singapore and draws out lessons for other nations. Housing in Singapore, he explains in this incisive analysis, is seen neither as a consumer good (as in the US) nor as a social right (as in the social democracies of Europe). The author goes on to look at the ways in which Singapore's planners have dealt with the problems of creating communities in a modern urban environment. He concludes that the success of the public housing programme has done much for Singapore.
Keywords: Public housing -- Singapore.; Public housing -- Government policy -- Singapore.; City planning -- Singapore.; Logement social -- Singapour.; Logement social -- Politique gouvernementale -- Singapour.; SOCIAL SCIENCE -- General.; BUSINESS & ECONOMICS -- Infrastructure.; City planning; Public housing; Public housing -- Government policy; Singapore